It Makes Sense, but I Just Don't Get It. Translators’ and End-users' Perspectives on the English to Chinese Community Translation of Health Texts - Teng, Wei (Auckland University of Technology, 2020)
This study aims to develop a set of assessment criteria aligned with the perspectives of end-users with a focus on the achievement of pragmatic equivalence in community translation (Taibi & Ozolins, 2016). Health translation (e.g. translation of healthcare texts) is of particular interest in this study as healthcare texts (e.g. healthcare pamphlets) often perform the pragmatic functions of informing and persuading the target audience to take actions in relation to managing their own health (Fischbach, 1962). I have adopted the frameworks of functional translation theories, systemic functional linguistics and Vygotskian social constructivism to firstly explain the different pragmatic nature of the translation of religious and literary texts from health translation; secondly to explain the social significance of achieving pragmatic equivalence in health translation; thirdly to define the pragmatic functions of health translation; and finally to establish a set of assessment criteria by considering the social construction process of meanings. A corpus comprising 15 English>Chinese health translation texts distributed in New Zealand has been assessed using the criteria by 15 professional translators and 15 elderly Chinese immigrants in New Zealand. The assessment results reveal a rather conflicting opinion on the translation quality in that, while the translators have a higher tolerance of expressions which do not sound natural in Chinese, believing that unnatural expressions do not fail pragmatic equivalence, the Chinese immigrants are more sensitive to unnatural expressions, and therefore are not informed or persuaded by the informational content delivered through the translations. In the light of these findings this study argues for the need to develop assessment criteria that can reflect translators’ awareness of pragmatic functions achieved in both the original texts and translated texts. It also discusses the need to develop student translators’ awareness that pragmatic equivalence is a product of both cross-cultural and cross-linguistic communication (House, 1981, 2001, 2006). The conclusion stresses the significance of looking at translation products from the end user perspective which involve holistic consideration of all three contextual meanings (i.e. ideational, interpersonal and textual meanings). After all, it is the end-users’ perspectives that the set of assessment criteria proposed in this study is aligned with, and it is their perspectives that we should always bear in mind as a translator, translation researcher and translation educator.
Keywords: Community Translation; Translation assessment; Pragmatic equivalence; Health translation